Complete genome sequences of virulent Mycoplasma capricolum subsp. capripneumoniae strains F38 and ILRI181 - Falquet, Laurent; Liljander, Anne M.; Schieck, Elise G.; Gluecks, Ilona V.; Frey, J.; Jores, Joerg (American Society for Microbiology, 2014)
Contagious caprine pleuropneumonia (CCPP) caused by Mycoplasma capricolum subsp. capripneumoniae is a severe epidemic affecting mainly domestic Caprinae species but also affects wild Caprinae species. M. capricolum subsp. capripneumoniae belongs to the “Mycoplasma mycoides cluster.” The disease features prominently in East Africa, in particular Kenya, Tanzania, and Ethiopia. CCPP also endangers wildlife and thus affects not only basic nutritional resources of large populations but also expensively built-up game resorts in affected countries. Here, we report the complete sequences of two M. capricolum subsp. capripneumoniae strains: the type strain F38 and strain ILRI181 isolated druing a recent outbreak in Kenya. Both genomes have a G+C content of 24% with sizes of 1,016,760 bp and 1,017,183 bp for strains F38 and ILRI181, respectively.